Bidirectional Regulation of NAD(P)H Quinone Dehydrogenase 1 Expression in Mouse Hepatic Stellate Cells- Acute versus Long-Term Ethanol Exposure - Yang, Hong; Zhang, Ningya; Guo, ZhongMao (Medical Research Archives, 2023)
Conclusions: Our findings suggest that ethanol upregulates NQO1 expression by activating the AhR-Nrf2 pathway. Long-term ethanol exposure sustains low level of AhR protein and diminishes the inducibility of its target genes Nrf2 and NQO1 by BaP. These findings will contribute to understanding the synergistic toxicity of ethanol and polycyclic aromatic hydrocarbon compounds, such as BaP.